Comparison of the transcutaneous bilirubinometers BiliCare and Minolta JM-103 in late preterm and term neonates. (16th September 2016) - Pratesi, Simone; Boni, Luca; Tofani, Lorenzo; Berti, Elettra; Sollai, Sara; Dani, Carlo
Abstract: Objectives : To assess the agreement of transcutaneous bilirubin (TcB) measurement with the Bilicare™ System in comparison to TcB measured with JM-103™ and total serum bilirubin (TSB). Methods : Caucasian infants with gestational age ≥35 weeks with non-hemolytic jaundice received TcB measurement with both Bilicare™ and JM-103™ devices. TSB was also obtained in infants at risk of phototherapy. Results : We studied 458 infants measuring TcB with Bilicare™ and JM-103™, correlating the results and with TSB. The mean difference ± 2SD between Bilicare™ and JM-103™ TcB was 2.02 ± 4.46 mg/dL and decreased from 2.88 ± 3.17 to 1.20 ± 4.55, and to −0.95 ± 4.58 mg/dL at mild, moderate and high TcB values, respectively. Conclusions : Bilicare™ and JM-103™ TcB measurements are well correlated, but Bilicare™ over-estimates TcB for mild and moderate values and under-estimates it for high values compared to JM-103™. This could increase the prescription of TSB measurements for less serious cases and decrease them in the most worrisome.